Temperate mountain grasslands: a climate‐herbivore hypothesis for origins and persistence. (4th October 2013) - Weigl, Peter D.; Knowles, Travis W.
ABSTRACT Temperate montane grasslands and their unique biotas are declining worldwide as they are increasingly being invaded by forests. The origin and persistence of these landscapes have been the focus of such controversy that in many areas their conservation is in doubt. In the USA some biologists have largely dismissed the grass balds of the Southern Appalachians as human artifacts or anomalous and transitory elements of regional geography, worthy of only limited preservation efforts. On the basis of information from biogeography, community ecology, regional history and palaeontology and from consideration of two other montane grassland ecosystems—East Carpathian poloninas and Oregon Coast Range grass balds—we hypothesize that these landscapes are more widespread than was formerly recognized; they are, in many cases, natural and ancient and largely owe their origin and persistence to past climatic extremes and the activities of large mammalian herbivores.